2020
DOI: 10.3389/fpls.2020.560169
|View full text |Cite
|
Sign up to set email alerts
|

Cell Dynamics in WOX5-Overexpressing Root Tips: The Impact of Local Auxin Biosynthesis

Abstract: Root stem cell niche functioning requires the formation and maintenance of the specific "auxin-rich domain" governed by directional auxin transport and local auxin production. Auxin maximum co-localizes with the WOX5 expression domain in the quiescent center that separates mitotically active proximal and distal root meristems. Here we unravel the interconnected processes happening under WOX5 overexpression by combining in vivo experiments and mathematical modeling. We showed that WOX5-induced TAA1mediated auxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
3
31
0
Order By: Relevance
“…Treating WOX5–GR-induced overexpression plants with differentiation-inducing CLE40 peptide indicated that only the first mature columella layer may undergo de-differentiation ( Berckmans et al , 2020 ). However, reproduction of the WOX5–GR-inducible overexpression experiments with a focus on cell division dynamics suggested that the observed multiple stem cell phenotype is exclusively caused by proliferation of columella stem cells ( Savina et al , 2020 ), which are subsequently maintained in their undifferentiated state.…”
Section: Wox5 As a Non-autonomous Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Treating WOX5–GR-induced overexpression plants with differentiation-inducing CLE40 peptide indicated that only the first mature columella layer may undergo de-differentiation ( Berckmans et al , 2020 ). However, reproduction of the WOX5–GR-inducible overexpression experiments with a focus on cell division dynamics suggested that the observed multiple stem cell phenotype is exclusively caused by proliferation of columella stem cells ( Savina et al , 2020 ), which are subsequently maintained in their undifferentiated state.…”
Section: Wox5 As a Non-autonomous Factormentioning
confidence: 99%
“…Upon induction of ectopic WOX5-GR expression, prior to any morphological change, the TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS1 ( TAA1 ) gene that is involved in auxin biosynthesis is up-regulated and has its expression domain expanded into the columella ( Savina et al , 2020 ). A similar pattern was observed for the auxin polar transporters PIN1 and PIN4, suggesting that WOX5 ectopic expression impacts both auxin biosynthesis and transport.…”
Section: Local Auxin Is Keymentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis , root growth is not compromised by genetic perturbations that result in alterations in the division patterns of the QC cells, suggesting that low division rate of the QC cells is not strictly necessary for the function and the organization of the root meristem under optimal growth conditions ( Vanstraelen et al, 2009 ; González-García et al, 2011 ; Cruz-Ramírez et al, 2013 ; Savina et al, 2020 ; Wang et al, 2020 ). The division of the QC cells has been shown to increase in frequency in older Arabidopsis seedlings ( Timilsina et al, 2019 ), and it can also be actively modulated to cope with the current needs of the root.…”
Section: Cell Cycle Regulation Of the Qc Cellsmentioning
confidence: 99%
“…In the root SCN, WOX5 promotes auxin accumulation in the QC by inducing the expression of the auxin biosynthetic enzymes YUCCA1 ( Tian et al, 2014 ), tryptophan aminotransferase of arabidopsis1 (TAA1; Savina et al, 2020 ), and by repressing the expression of auxin conjugation genes ( Gonzali et al, 2005 ). As WOX5 expression is induced by auxin in the QC ( Sarkar et al, 2007 ), this establishes an auxin—WOX5-positive feedback loop in these cells.…”
Section: Hormonal Regulation Of Qc Mitotic Activitymentioning
confidence: 99%